Quantitative analyses of diameter and running pattern of choroidal vessels in central serous chorioretinopathy by en face images - Shiihara, Hideki (Sci Rep, 2020)
This study was to investigate the choroidal vessels in eyes with central serous chorioretinopathy (CSC) quantitatively. We studied 41 CSC eyes and their fellow eyes, and 41 normal eyes of 41 age-adjusted individuals. En-face optical coherence tomography image of the top 25% slab of Haller’s layer was analyze. The mean vessel area, vessel length, and vessel diameter were calculated. The running pattern of the vessels was quantified and used to determine the degree of symmetry, the “symmetry index”. The vessel area of CSC eyes was not significantly different from that of fellow eyes but significantly larger than that of normal eyes. The vessel length of CSC eyes was not significantly different from fellow eyes but significantly shorter than that of normal eyes. The mean vessel diameter was larger in CSC eyes than in the fellow eyes and the normal eye. The symmetry index was not significantly different in CSC eyes from that of their fellow eyes but was smaller than that of normal eyes. The quantitative analysis showed that eyes with CSC had larger choroidal vessels and asymmetrical vessels running in Haller’s layer.